Cost-Effectiveness Analysis of Antibiotic Therapy for Community-Acquired Pneumonia at Mimika Regional Hospital, Central Papua - Arifin, Bustanul; Sattu, Fidel Yoel Junovray; Saud, Anshar (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide, affecting the lower respiratory tract. It is caused by diverse pathogens, including bacteria, viruses, fungi, and chemical exposures. Antibiotics, such as ceftriaxone, are widely used for treatment. However, the high economic burden associated with CAP management necessitates a cost-effectiveness analysis to optimize treatment strategies.Objectives: This study aimed to evaluate the cost-effectiveness of three antibiotic regimens—co-amoxiclav, meropenem + levofloxacin, and ceftriaxone—for CAP inpatients at Mimika Hospital, Indonesia, to identify the most efficient therapeutic option.Methods: A retrospective, cross-sectional observational study was conducted using medical records of CAP patients admitted to Mimika Hospital between January and December 2021. Inclusion criteria were patients aged ≥18 years who received a single antibiotic regimen. Treatment effectiveness was assessed based on hospitalization duration (≤3 days) and physician-reported recovery. Cost-effectiveness was evaluated using the Average Cost-Effectiveness Ratio (ACER).Results: A total of 120 pneumonia inpatients were analyzed, predominantly male (60%) and aged 26–45 years (34%). The most frequently administered antibiotic was ceftriaxone (51%), followed by co-amoxiclav (29%) and meropenem + levofloxacin (20%). Co-amoxiclav demonstrated the highest clinical effectiveness (88.57%) and the lowest median total cost (IDR 2,696,114), resulting in the lowest ACER value (IDR 2,696,114/effectiveness unit) and a dominant ICER status. In contrast, meropenem + levofloxacin showed moderate effectiveness (75%) at the highest cost (IDR 3,088,961), with an ICER of IDR 18,538.64. Ceftriaxone had the lowest effectiveness (65.57%) and the highest ACER (IDR 44.443,22), indicating poor cost-efficiency. These findings position co-amoxiclav as the most cost-effective regimen across both clinical and economic parameters.Conclusion: Co-amoxiclav is the most cost-effective antibiotic regimen for CAP inpatients at Mimika Hospital, offering optimal therapeutic outcomes at a lower cost. These findings support its recommendation as the first-line treatment for CAP in similar healthcare settings